Comparative analysis of playing patterns between top and bottom-ranked teams in the FIFA Futsal World Cup 2024 - Sabariman, Hazim Muhaimin; Che Ab Llah, Che Ameer Aqeel; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Abu Kasim, Nurul Ain; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study compares tactical patterns and performance indicators between the top and bottom three teams of the FIFA Futsal World Cup 2024, addressing a gap in tier-based comparative analysis. By evaluating KPIs such as scoring efficiency, defensive organization, pressing intensity, and movement patterns within a single tournament framework, the research identifies the strategic variables that distinguish elite performance. These findings offer actionable insights for coaches and analysts to refine training methodologies and tactical planning for high-level futsal competitions.